A outra face de narciso: cultura do consumo e beleza do corpo na sociedade contemporânea - Diniz, Márcia Ramalho (2014)
Technological and industrial changes in recent times historically defined the transformations of capitalist societies. The development experienced by modernity brings along with itself the means of production, which increased in quantity, speed and diversity. Thus, the relationship between production and consumption has intensified and the market grew, increasing the number of goods available to the population. In this consumer and mass society, the body is gaining more prominence. The appreciation of the body physical appearance is the result of this overexposure in the public space, where the stereotype of a beautiful body, healthy body, shapely body is dictated by the fashion and beauty industry transforming it into an object of consumption. Although, this study aims to analyze the beauty category in its evolution, it changes the perspective on the body and consumer culture in contemporary society, with reference to the physical education professionals working in gyms in João Pessoa city. Regarding to the methodology, research approach is a dialectical-criticism, theoreticalpractical, with a predominantly qualitative analysis perspective. The research involved 14 physical education professionals, working in gyms in João Pessoa city. One semi-structured interview, recorded by the researcher and the instrument used for analysis was the content analysis which was performed. We conclude that behind a discourse of welfare and health, there is a whole ideology that appeals to an ideal of unattainable beauty, characteristic of contemporary society that survives of a overconsumption culture, leading individuals to a constant dissatisfaction. It means that body beauty today, this consumer society, keep the dominant Platonic ideals of order, symmetry, a beauty that is in the object, in appearance. Despite talking about health, quality of life, all this only justifies the way the gyms, surgeries, medications, disorderly quest to maintain an optimal pattern imposed by consumer society, where the physical education professional mostly continues playing the idea of beauty reduced to physical standards; and reduced health to the quest for the perfect body models reported in the media.